1997
DOI: 10.1055/s-0038-1665407
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Exercise Induces Release of Soluble P-Selectin in Patients with Intermittent Claudication

Abstract: SummaryControversy exists as to whether exercise in patients with intermittent claudication causes a harmful biochemical effect associated with an ischaemia-reperfusion injury of skeletal muscle. We report on exercise-induced changes in neutrophil activation, soluble P-selectin and von Willebrand factor in 34 patients with intermittent claudication and 12 matched controls.Von Willebrand factor (vWF) showed a cyclical pattern of response to exercise in control subjects (rising from 103 ± 8 to 119 ± 7 U/dl); cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 22 publications
7
26
0
Order By: Relevance
“…the exercise metabolome) was studied separately for each treatment period (study appointments A, B and C). Clustering was not evident in healthy subjects (results not shown), which is in line with previous studies [7,23,24]. Figure 2 depicts the PC-DA models, based on plasma CPMG NMR profiles from the claudicants obtained in periods A and C.…”
Section: Blood Plasma Exercise Metabolome As Observed By Nmrsupporting
confidence: 88%
See 2 more Smart Citations
“…the exercise metabolome) was studied separately for each treatment period (study appointments A, B and C). Clustering was not evident in healthy subjects (results not shown), which is in line with previous studies [7,23,24]. Figure 2 depicts the PC-DA models, based on plasma CPMG NMR profiles from the claudicants obtained in periods A and C.…”
Section: Blood Plasma Exercise Metabolome As Observed By Nmrsupporting
confidence: 88%
“…The vitamin intervention led to an overall decrease in F2-isoprostane concentration, and a statistically significant effect of exercise was no longer observed. As expected [7,23,24], no significant effects on F2-isoprostane concentrations were observed in the control group.…”
Section: Biochemical and Clinical Variablessupporting
confidence: 78%
See 1 more Smart Citation
“…Platelet activation is known to in¯uence BV [26] and our pre-treatment ®nding of an increase in soluble Pselectin after exercise may indicate early, reversible platelet activation in claudication [4], concurring with Kirkpatrick et al [22]. As P-selectin is not normally expressed on resting platelets, its detection on the platelet surface is considered an index of secretion since it is contained in platelet a-granules [41].…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore activated leukocytes release thromboxane A2, which in addition to be a vasoconstrictor, promotes platelet aggregation [27], so inducing the phenomenon of platelet plugging. To this phenomenon in claudicants may also participate overexpression of P-selectin [28,29] which mediates platelet-endothelium interaction [30]. Consistent with the observation by Neumann et al [26], our group observed that in the claudicant limb, but not in the healthy legs of the control group, maximal exercise increased the transfemoral venous-arterial difference of the neutrophil myeloperoxidase (MPOx) content [31], an index of neutrophil activation and a well established marker of inflammation [32].…”
Section: Effect Of Ischemia On Endotheliumsupporting
confidence: 86%